Protein Kinase D1 Is Essential for Contraction-induced Glucose Uptake but Is Not Involved in Fatty Acid Uptake into Cardiomyocytes - Dirkx, Ellen (American Society for Biochemistry and Molecular Biology, 2012)
Increased contraction enhances substrate uptake into cardiomyocytes via translocation of the glucose transporter GLUT4 and the long chain fatty acid (LCFA) transporter CD36 from intracellular stores to the sarcolemma. Additionally, contraction activates the signaling enzymes AMP-activated protein kinase (AMPK) and protein kinase D1 (PKD1). Although AMPK has been implicated in contraction-induced GLUT4 and CD36 translocation in cardiomyocytes, the precise role of PKD1 in these processes is not known. To study this, we triggered contractions in cardiomyocytes by electric field stimulation (EFS). First, the role of PKD1 in GLUT4 and CD36 translocation was defined. In PKD1 siRNA-treated cardiomyocytes as well as cardiomyocytes from PKD1 knock-out mice, EFS-induced translocation of GLUT4, but not CD36, was abolished. In AMPK siRNA-treated cardiomyocytes and cardiomyocytes from AMPKα2 knock-out mice, both GLUT4 and CD36 translocation were abrogated. Hence, unlike AMPK, PKD1 is selectively involved in glucose uptake. Second, we analyzed upstream factors in PKD1 activation. Cardiomyocyte contractions enhanced reactive oxygen species (ROS) production. Using ROS scavengers, we found that PKD1 signaling and glucose uptake are more sensitive to changes in intracellular ROS than AMPK signaling or LCFA uptake. Furthermore, silencing of death-activated protein kinase (DAPK) abrogated EFS-induced GLUT4 but not CD36 translocation. Finally, possible links between PKD1 and AMPK signaling were investigated. PKD1 silencing did not affect AMPK activation. Reciprocally, AMPK silencing did not alter PKD1 activation. In conclusion, we present a novel contraction-induced ROS-DAPK-PKD1 pathway in cardiomyocytes. This pathway is activated separately from AMPK and mediates GLUT4 translocation/glucose uptake, but not CD36 translocation/LCFA uptake.